Identification of key bacterial players during successful full-scale soil field bioremediation in Antarctica - Martinez Alvarez, Lucas Manuel; Bolhuis, Henk; Mau, Goh Kian; Kok Gan, Chan; Sing, Chan Chia; Mac Cormack, Walter Patricio; Ruberto, Lucas Adolfo Mauro (International Biodeterioration & Biodegradation)
The Antarctic continent is not exempted from anthropogenic contamination. Diesel spills on Antarctic soils occur frequently. There, extreme climate conditions and the scarce infrastructure, cause that few remediation strategies become feasible. Bioremediation has proven to be an effective approach for hydrocarbon-contaminated soils in Antarctica, allowing the removal of up to 80% of the contaminant by biostimulating soil microbial communities in biopiles. However, little is known on the changes that this treatment cause in the microbial communities, and how may this knowledge be used for future bioremediation schemes. In this work, we analyzed the changes in the bacterial community composition of biostimulated (BS) and control (CC) biopiles at Carlini Station (Arg.), Antarctica, from our previously reported “on-site” bioremediation scheme. The results showed that hydrocarbon biodegradation in Antarctic soils was accompanied by a significant change in bacterial community composition, with a progressive differentiation between the treated (BS) and non-treated (CC) systems as a function of time. Microbial diversity decreased in the BS system due to the enrichment in genera Pseudomonas, Rhodococcus, and Rhodanobacter, that seemed to follow an r/K (or copiotrophic/oligotrophic) strategist dynamic, in which Pseudomonas increased significantly at the early stages of the treatment (from initial 23.8% up to 33.2% at day 20, r strategist), while Rhodococcus and Rhodanobacter (K strategists) became dominant since day 20 and until the end of the experiment (from 5.4% to 2.4% at T = 0 days, up to 17.4% and 14.0% at the end of the experiment, respectively). In the control system, Sphingomonas (14.0% at T = 30 days), Pseudomonas (10.5% at T = 30 days), and Rhizorhapis (9.9% at T = 30 days) were the genera with higher relative abundance during the entire treatment period, with no short-term shifts in dominances and a more diverse and even bacterial community. Fil: Martinez Alvarez, Lucas Manuel. Ministerio de Relaciones ...